1983
DOI: 10.1007/bf02908693
|View full text |Cite
|
Sign up to set email alerts
|

An improved method for determining β-glucan in wort and beer by use of Calcofluor

Abstract: An improved method for the determination of~glucan in beer and wort employing the fluorochmme Calcofluor is described. Dimethylsulfoxid (20~ (v/v)) was used to obtain a reproducible binding ratio of Calcofluor to I}-glucan. The formed complex was precipitated by 77% ethanol and separated by centrifugation. The precipitate was dissolved in a glycine/NaOH buffer at pH ~ 10.0 and fluorescence was measured in a spectrofluorometer. The method correlates well with the established ammoniumsulphate precipitation metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…Over the whole of the seed, a clear‐cut transition from non‐degraded to degraded endosperm was visible, which was formerly described as an enzymatic front that migrated centripetally from scutellum and aleurone inwards (Selvig et al ., 1986). This front resulted in the loss of β‐glucan staining, which meant that at least the degree of polymerization was decreased to levels below 55 (Jørgensen, 1983). The outer arabinoxylan cell walls remained intact, although the microstructure was less clear.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the whole of the seed, a clear‐cut transition from non‐degraded to degraded endosperm was visible, which was formerly described as an enzymatic front that migrated centripetally from scutellum and aleurone inwards (Selvig et al ., 1986). This front resulted in the loss of β‐glucan staining, which meant that at least the degree of polymerization was decreased to levels below 55 (Jørgensen, 1983). The outer arabinoxylan cell walls remained intact, although the microstructure was less clear.…”
Section: Resultsmentioning
confidence: 99%
“…A 0.1 g L −1 solution of calcofluor was applied for 3 min. It was previously calculated that calcofluor binds to β‐glucan with a degree of polymerization of 55 and higher (Jørgensen, 1983).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The I]-glucans in wort and beer can be measured by the AMS-method or as previously described by the use of Calcofluor (CEP-method, 15,16). The relationship between the values determined by these methods and the viscosity of wort and beer has been investigated (14,16,19), and it was shown that the 15-glucan content could not fully explain the variation in viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between the values determined by these methods and the viscosity of wort and beer has been investigated (14,16,19), and it was shown that the 15-glucan content could not fully explain the variation in viscosity.…”
Section: Introductionmentioning
confidence: 99%